Development of calorimetry methodology for beam current measurement of the Linear IFMIF Prototype Accelerator (LIPAc) - Nishiyama, K.; Knaster, J.; Okumura, Y.; Marqueta, A.; Pruneri, G.; Scantamburlo, F.; Sakamoto, K.; Sugimoto, M.; Kasugai, A.; Hirata, Y.; Kondo, K.; Ikeda, Y.; et al. (Fusion engineering and design, 2018)
•Optimization of the beam current measurement of the injector of the LIPAc.•To check the accuracy of the measurement, an electric heater was inserted in the cooling loop and the correlation between applied and measured power was obtained.•Using the same heater, optimal flow rates of the cooling water for measured power level were examined.•Validation of the current results with calorimetry were obtained by deviating the secondary electrons thanks to the installation of permanent magnets. The goal of LIPAc (Linear IFMIF Prototype Accelerator) is to achieve a 125mA, 9 MeV, CW (continuous wave, i.e. 100% duty cycle) deuteron beam with an average beam power of 1.125 MW. In the beam current measurement, it is considered that calorimetric measurement is advantageous for high current and CW operations since it is not subject to secondary electrons, etc. In calorimetric measurements, it is necessary to measure the temperature rise of the cooling water as accurately as possible. We applied this method to LIPAc proton beams at the Beam Stop unit. In order to check the reliability, we inserted a heater in the cooling loop as a heat source and obtained correlation between the applied and measured power, which was found to be 1.0. Moreover, using this heater, accuracy of this measurement with respect to the flow rate of the cooling water was investigated. Due to heat transfer and the fluctuations of water temperature, etc., there is a range of flow rates in which the measurement error can be minimized with our calorimetric measurement system.